Online Gamification Platforms for Practicing EFL Students’ Reading Skills: A Systematic Review - Dinda Kamila Chaidir; Muhamad Aziz Muslim; Muchlas Suseno; Darmahusni Darmahusni (Universitas Muhammadiyah Semarang, 2023)
Currently, gamification is one of the highly discussed topics among English as a Foreign Language (EFL) practitioners. It is worth mentioning that the rising interest in Information and Communications Technology (ICT) increases the preference for learning towards online gamification. This study aims to provide a review regarding online gamification platforms for practicing EFL students’ reading skills. This research used library research method and followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline developed by Page et al. to collect and reduce data, and finally present a transparent, complete, and accurate review. The data were 20 articles published worldwide between 2012 and 2022 and sourced from journal finders of ScienceDirect, Springer, Taylor & Francis, and Google Scholar. Furthermore, this study used NVIVO 14 and Microsoft Excel 2016 to analyze the selected data and Mendeley for reference management. The results showed that Kahoot!, Quizizz, Socrative, Bibliobattle, Classcraft, ClassDojo, Duolingo, Genially, Into the Book, M-reader, Memrise, Padlet, Quizlet, and ReadTheory.org are feasible to be used to practice EFL students’ reading skills, with Kahoot! and Quizizz as the most popular. In addition, the context of the studies involved as the research data such as the year published, educational level, national origins, and methodologies were also mentioned. Further, it is implied that EFL teachers can use online gamification platforms to leverage not only students’ motivation and engagement in practicing students’ reading skills but also their learning achievements through enjoyable and interactive learning while allowing students to acquire ICT skills.